MENINGKATKAN HASIL BELAJAR PAI MELALUI COOPERATIVE LEARNING TIPE WHAT’S MY LINE KELAS V SD - Hamim (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2013)
The research was based on the low value of the results of repeated Islamic Education ( PAI) on the subject of Conduct commendable deeds , it is marked number of students who achieve the KKM is still low at 70 % . Though the expected target is 100 % . This research aimed at using models Jigsaw Cooperative Learning in a learning mode of Islamic Education ( PAI ) fifth grade elementary school subjects Doing commendable deeds . The method used in this study was Classroom Action Research ( CAR), which adapted the model of Kemmis and Mc . Taggart with two cycles, each cycle performed two acts . The research subjects were students in grade 28 in total V. . The results using the model of Type Jigsaw Cooperative Learning in History teaching duapeningkatan Prophet shows that improvement in the quality of teaching and improving student learning outcomes . 1 cycle of learning process is still less than optimal quality of learning due to lack of communication skills among students in the group , while in the second cycle students seemed to enjoy the learning process and are very happy to work within their own group , so that the students' grades in the history of the Prophet's teaching has increased